Pengaruh Literasi dan Minat Baca Terhadap Prestasi Belajar Siswa di MIN Sibuhuan - Nurhalimah Harahap; Era Mutiah; Risky Natama Lubis (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2023)
This study aims to: (1) To determine the literacy of fifth grade students at MIN Sibuhuan. (2) To find out the reading interest of class V MIN Sibuhuan students. (3) To determine the effect of literacy and interest in reading on the learning achievement of class V MIN Sibuhuan students. The type of research used is quantitative research. Data collection techniques in this research were obtained through tests, observation and documentation. The data analysis techniques used are validity and reliability tests, normality and homogeneity tests and hypothesis testing. Based on the results of the study it was concluded that: (1) Literacy of class V students of Sibuhuan MIN has an average of 79.2, the highest score is 90 and the lowest score is 60. (2) The reading interest of class V students of Sibuhuan MIN has an average of 78, 8, the highest score is 90 and the lowest score is 60. (3) The effect of literacy and interest in reading on student achievement in class V MIN Sibuhuan. In the pretest the mean is 59.6, the highest score is 90 and the lowest score is 30. Meanwhile, student achievement in the posttest for the mean is 76.4, the highest score is 90 and the lowest score is 50. So the increase in learning achievement from the pretest is quite significant ie from 48% to 84%.